2018
DOI: 10.14814/phy2.13852
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 suppresses glucagon secretion in human pancreatic alpha-cells by inhibition of P/Q-type Ca2+ channels

Abstract: Glucagon is the body's main hyperglycemic hormone, and its secretion is dysregulated in type 2 diabetes mellitus (T2DM). The incretin hormone glucagon‐like peptide‐1 (GLP‐1) is released from the gut and is used in T2DM therapy. Uniquely, it both stimulates insulin and inhibits glucagon secretion and thereby lowers plasma glucose levels. In this study, we have investigated the action of GLP‐1 on glucagon release from human pancreatic islets. Immunocytochemistry revealed that only <0.5% of the α‐cells possess de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 100 publications
6
49
0
1
Order By: Relevance
“…Our data suggests that physiological (picomolar) concentrations of GLP-1 exert their glucagonostatic effects via mechanisms that are (at least in part) intrinsic to the glucagon-secreting α-cells and that are independent of paracrine effects from the neighboring islet cells. A similar conclusion was previously made for pharmacological (nanomolar) concentrations of GLP-1(7-36) (5,6).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our data suggests that physiological (picomolar) concentrations of GLP-1 exert their glucagonostatic effects via mechanisms that are (at least in part) intrinsic to the glucagon-secreting α-cells and that are independent of paracrine effects from the neighboring islet cells. A similar conclusion was previously made for pharmacological (nanomolar) concentrations of GLP-1(7-36) (5,6).…”
Section: Discussionsupporting
confidence: 86%
“…insulin and somatostatin, respectively) within the pancreatic islets (8). Yet, GLP-1 (when tested at nonphysiological nanomolar levels) robustly inhibited glucagon secretion in isolated islets by mechanisms that cannot be accounted for by paracrine signals (5,6). We have proposed that this effect is mediated by activation of the few GLP-1 receptors present in α-cells and that this, via a small increase in cAMP, results in inhibition of the voltagegated Ca 2+ channels linked to exocytosis of glucagon-containing secretory granules.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies using antibodies, reporter animals and agonist-fluorophores have shown only ∼1-10% GLP1R expression in mouse and rat α-cells, in line with the low transcript abundance 7,19,33,45 , despite reports that GLP-1 can directly suppress glucagon release. 34,46 Our data are in general concordance with these findings, but demonstrate an increase in detection capability for native GLP1R. This improvement is likely related to the superior SNR of LUXendin645 compared to mAb and agonist-fluorophore, increasing the ability to resolve relatively low GLP1R levels.…”
Section: Discussionsupporting
confidence: 84%
“…It has been documented that suppression of glucagon secretion can be mediated at the systemic, paracrine or intrinsic level (12). As a systemic modulator, GLP-1 inhibits glucagon secretion; however, there are controversies as to whether GLP-1 directly inhibits glucagon secretion from α cells by signaling through the alpha cell GLP-1R (13)(14)(15), or indirectly by increasing inter-islet somatostatin or insulin secretion (13,16). Glucagon secretion is also suppressed by paracrine signaling through the insulin, somatostatin and GABA A receptors on the α cell (16)(17)(18) At an intrinsic level, glucose directly or indirectly inhibits glucagon secretion from the α cell (19)(20)(21)(22) by altering downstream activities of Ca 2+ channels, K ATP channels (23), and trafficking of secretory granules (24).…”
Section: Introductionmentioning
confidence: 99%